Zero-divisor Graphs of Ore Extensions Over Reversible Rings. Issue 4 (1st December 2016) - Hashemi, E.; Amirjan, R.
Abstract: Let R be an associative ring with identity. First we prove some results about zero-divisor graphs of reversible rings. Then we study the zero-divisors of the skew power series ring R[\![ x; α ]\!], whenever R is reversible α -compatible. Moreover, we compare the diameter and girth of the zero-divisor graphs of Γ ( R ), Γ ( R[x; α, δ ] ), and Γ ( R[\![ x; α ]\!] ), when R is reversible and ( α, δ ) -compatible.